1970
DOI: 10.1161/01.res.26.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Blood Flow in the Normal and the Sympathectomized Dog Hind Limb during Graded Exercise

Abstract: The possibility of sympathetic vasoconstrictor control of blood flow to active muscles was studied in dogs during graded exercise by comparing the blood flow in the normal with that in the Sympathectomized hind limb. Blood flow was measured by electromagnetic flow transducers around each external iliac artery, or inferred from the oxygen saturation of blood samples from the common iliac veins. The dogs either ran for successive periods of 3 minutes at 5.5 km/hr and grades of 0, 7, 14, 21, and 28% or ran each l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 19 publications
0
51
0
Order By: Relevance
“…However, the functional consequence of reflex-sympathetic activation in contracting skeletal muscle has been the subject of considerable debate. Previous studies in intact animals and humans have suggested that sympathetic vasoconstriction in contracting muscle is both ( a ) well preserved (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), thereby partially offsetting metabolic vasodilation to maintain blood pressure (29); and ( b ) largely negated by metabolic vasodilation (30)(31)(32)(33)(34)(35)(36)(37)(38), thereby optimizing muscle perfusion. The latter concept, initially termed "functional sympatholysis" (30) recently has been extended by reductionist microcirculatory preparations (39)(40)(41)(42)(43)(44)(45) demonstrating that certain local metabolic consequences of contraction (e.g., intramuscular acidosis, hypoxia) interfere with specific signal transduction pathways mediating alpha-adrenergic vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functional consequence of reflex-sympathetic activation in contracting skeletal muscle has been the subject of considerable debate. Previous studies in intact animals and humans have suggested that sympathetic vasoconstriction in contracting muscle is both ( a ) well preserved (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), thereby partially offsetting metabolic vasodilation to maintain blood pressure (29); and ( b ) largely negated by metabolic vasodilation (30)(31)(32)(33)(34)(35)(36)(37)(38), thereby optimizing muscle perfusion. The latter concept, initially termed "functional sympatholysis" (30) recently has been extended by reductionist microcirculatory preparations (39)(40)(41)(42)(43)(44)(45) demonstrating that certain local metabolic consequences of contraction (e.g., intramuscular acidosis, hypoxia) interfere with specific signal transduction pathways mediating alpha-adrenergic vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…P2X receptors on vascular smooth muscle cells are preferentially stimulated by ATP from sympathetic nerve endings (17). Although two recent studies (1,19) showed that P2X-receptor stimulation produces vasoconstriction in the hindlimb of anesthetized cats and rats, it is unknown whether stimulation of P2X receptors in the arterial vasculature of skeletal muscle will produce vasoconstriction during exercise.In the past, the ability of the sympathetic nervous system to restrain blood flow in active skeletal muscle has been questioned (14,24,26). However, there is clear and convincing evidence that there is sympathetic restraint of skeletal muscle hyperemia during exercise (3,5,20,34,35,43).…”
mentioning
confidence: 99%
“…In the past, the ability of the sympathetic nervous system to restrain blood flow in active skeletal muscle has been questioned (14,24,26). However, there is clear and convincing evidence that there is sympathetic restraint of skeletal muscle hyperemia during exercise (3,5,20,34,35,43).…”
mentioning
confidence: 99%
“…If actiIn normal subjects and normal experimental animals, In this study we sought to investigate this possibility by examining the effect of a-adrenergic blockade on vascular resistance, blood flow, and lactate release in the leg during maximal exercise in patients with heart failure. Leg resistance and blood flow were used as indexes of skeletal muscle resistance and flow, respectively; flow to nonmuscular tissue makes up only a small portion of leg blood flow during exercise.23 Systemic and leg oxygen uptake and leg lactate release were used as indexes of the adequacy of oxygen delivery to working muscle.24 21 To evaluate changes in these variables during exercise, the variables were compared at identical work times. Exercise level influences muscle blood flow and metabolism.…”
Section: Methodsmentioning
confidence: 99%